Engineering location-based services in the web - Gordillo, Silvia Ethel; Bazzocco, Angel Javier; Rossi, Gustavo Héctor; Laurini, Robert (2005)
In this chapter, we will present a modular approach for building evolvable location- based services in the context of Web applications. We first motivate our research by discussing the state of the art of location-based services; next we analyze which design problems we face while building this kind of application, stressing those problems related with the application's evolution. We present an object-oriented design approach for engineering location-based applications that effectively supports the evolution of these applications rather than their revolution and give a few examples of its use. We finally discuss some further research issues not explicitly addressed in this chapter.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Web Engineering. Principles and Techniques, London:Woojong Suh, 2005; pp. 114-130.
Keywords: APLICACIONES WEB; DESARROLLO DE APLICACIONES